Single-stage inferior vena caval intravenous leiomyomatosis excision - Karthigesu Aimanan; Kean, Leong Koay; Mohd Firdaus Mohd Hayati; Hafizan Mohd Tajri (BMJ Publishing Group, 2022)
Intravascular tumour extension can occur in many different types of cancer. Those with the highest tendency include renal cell carcinoma, adrenal cortical carcinoma and hepatocellular carcinoma. Inferior vena cava (IVC) tumour thrombus in gynaecological malignancy is rarely reported. We present a report on a female patient with extensive IVC tumour thrombus (intravenous leiomyomatosis) with concurrent intrauterine leiomyomatosis. She underwent a single-stage procedure, involving laparotomy and a sternotomy to remove her pelvic tumour, as well as the intracaval and intracardiac thrombus. The clinical presentation and management of this rare tumour will be detailed in this case report.